2020
DOI: 10.3390/plants9020199
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chloroplast Genomics of Endangered Euphorbia Species: Insights into Hotspot Divergence, Repetitive Sequence Variation, and Phylogeny

Abstract: Euphorbia is one of the largest genera in the Euphorbiaceae family, comprising 2000 species possessing commercial, medicinal, and ornamental importance. However, there are very little data available on their molecular phylogeny and genomics, and uncertainties still exist at a taxonomic level. Herein, we sequence the complete chloroplast (cp) genomes of two species, E. larica and E. smithii, of the genus Euphorbia through next-generation sequencing and perform a comparative analysis with nine related genomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 71 publications
8
27
3
Order By: Relevance
“…Repetitive sequences in plastid genomes play an essential role in population genetics and biogeography studies [51,52], and these repeats may result from slipped-strand mispairing and improper recombination [53]. In this study, short dispersed repeats (SDRs) analysis found 22 forward, 0 reverse, 0 complement and 20 palindromic repeats in the plastid genome of B. chinense ( Figure 4A), of which 32 were 30-40 bp in length, 7 were 41-50 bp in length, and 3 exceeded 70 bp in length ( Figure 4B).…”
Section: Repetitive Sequences Analysismentioning
confidence: 99%
“…Repetitive sequences in plastid genomes play an essential role in population genetics and biogeography studies [51,52], and these repeats may result from slipped-strand mispairing and improper recombination [53]. In this study, short dispersed repeats (SDRs) analysis found 22 forward, 0 reverse, 0 complement and 20 palindromic repeats in the plastid genome of B. chinense ( Figure 4A), of which 32 were 30-40 bp in length, 7 were 41-50 bp in length, and 3 exceeded 70 bp in length ( Figure 4B).…”
Section: Repetitive Sequences Analysismentioning
confidence: 99%
“…Pseudogenization or loss of plastid genes is often accompanied by the transfer of the gene to the nuclear genome or substitution by a nuclear gene that is already targeted to the plastid 27,66 . Plastid gene loss and transfer to the nucleus or substitution by a dual targeted nuclear gene targeted to organelles has been recorded for several genes across multiple angiosperm lineages [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . The focus of this study was to use transcriptome data to bioinformatically identify the fate of two plastid genes, rpl32 and rps16, in Euphorbia schimperi that have either been lost or pseudogenized.…”
Section: Discussionmentioning
confidence: 99%
“…Most angiosperm plastomes have a highly conserved gene content ranging between 120-130 genes out of the approximately 1000 to 8000 genes that were present in the cyanobacterial ancestor 3 . There are some exceptions in various lineages including losses/transfers of infA in most rosids 4,5 , rpl33 in some legume lineages 6,7 , rpl32 in Salicaceae 8,9,10,11 , Rhizophoraceae 10 , Ranunculaceae 12 , Passi oraceae 13,14 and Euphorbiaceae 15,16,17 , rps16 in various legumes 6,18,19,20,21 , Salicaceae 8,9,22 , Passi oraceae 14 and Euphorbiaceae [15][16][17]23,24,25 , rpl22 in Fabaceae, Fagaceae, Passi oraceae, and Salicaceae 13,14,26,27 and rpl20 in Passi oraceae 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations